ЖЕЛІЛІК ЖОСПАРЛАУ ЖӘНЕ БАСҚАРУ МОДЕЛІНІҢ КӨМЕГІМЕН ТҰРҒЫН ҮЙ ҚҰРЫЛЫСЫ ЖОБАСЫН ТАЛДАУ (Journal of Economic Research & Business Administration, 2015)
This article describes the analysis of projects under uncertainty, using a network model of planning and management.